Investing in venture capital funds in the countries of Central and Eastern Europe - Prtenjača Mažer, Karmen (Oeconomica Jadertina, 2019)
Venture capital investment funds are an important part of the financial system since they provide capital to companies that do not have enough equity and cannot stipulate optimal financial arrangements with other financial intermediaries. Setting up a venture capital investment fund requires funding raised from a variety of sources. The aim of the paper is to present investment in venture capital funds in the countries of Central and Eastern Europe (CEE), which is significantly behind the rest of Europe. The problem faced by venture capital funds in CEE countries is that investors do not invest in venture capital funds because of the high level of corruption, fear of unsettled property law aspects, and lack of knowledge of local entrepreneurs leading to poor corporate governance. The achieved results show that foreign investors still do not show sufficient interest in investing in venture capital funds in CEE countries. Given the lack of funds to invest in venture capital funds, they are not developing as in the rest of Europe and thus the demand for this type of financing by entrepreneurs in CEE countries is limited.
Keywords: investment; corruption index; legal restrictions; venture capital investment funds; Central and Eastern Europe; Croatia